A cross-sectional analysis of the relationship between tobacco and alcohol outlet density and neighbourhood deprivation. (December 2015) - Shortt, Niamh; Tisch, Catherine; Pearce, Jamie; Mitchell, Richard; Richardson, Elizabeth; Hill, Sarah; Collin, Jeff
Abstract Background There is a strong socio-economic gradient in both tobacco-and alcohol-related harm. One possible factor contributing to this social gradient may be greater availability of tobacco and alcohol in more socially-deprived areas. A higher density of tobacco and alcohol outlets is not only likely to increase supply but also to raise awareness of tobacco/alcohol brands, create a competitive local market that reduces product costs, and influence local social norms relating to tobacco and alcohol consumption. This paper examines the association between the density of alcohol and tobacco outlets and neighbourhood-level income deprivation. Methods Using a national tobacco retailer register and alcohol licensing data this paper calculates the density of alcohol and tobacco retail outlets per 10, 000 population for small neighbourhoods across the whole of Scotland. Average outlet density was calculated for neighbourhoods grouped by their level of income deprivation. Associations between outlet density and deprivation were analysed using one way analysis of variance. Results There was a positive linear relationship between neighbourhood deprivation and outlets for both tobacco (p <0.001) and off-sales alcohol (p <0.001); the most deprived quintile of neighbourhoods had the highest densities of both. In contrast, the least deprived quintile had the lowest density of tobacco and both off-sales and on-sales alcohol outlets. Conclusions The social gradient evident in alcohol and tobacco supply may be a contributing factor to the social gradient in alcohol- and tobacco-related disease. Policymakers should consider such gradients when creating tobacco and alcohol control policies. The potential contribution to public health, and health inequalities, of reducing the physical availability of both alcohol and tobacco products should be examined in developing broader supply-side interventions.